2016
DOI: 10.1515/johr-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gibberellic Acid and Potassium Foliar Sprays on Productivity and Physiological and Biochemical Parameters of Parthenocarpic Cucumber cv. ‘Seven Star F1

Abstract: A study was carried out to evaluate the potential of exogenously applied potassium nitrate [1.0 g·dm−3(K1), 2.5 g·dm−3(K2) and 5 g·dm−3(K3)] plus gibberellic acid (GA3) [0.005 g·dm−3(G1), 0.01 g·dm−3(G2) and 0.015 g·dm−3(G3)] on the growth and development of the cucumber (Cucumis sativusL.) ‘Seven Star F1’ during various growth stages (40, 55 and 70 days after sowing). Treatment of plants with K plus GA3stimulated growth shortened the fruit maturation period and increased quality compared with non-sprayed cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…They referred this enhancing effect to the physiological role of potassium in stimulating enzymes responsible for carbohydrate synthesis and production of energy as well as protein synthesis through its role in activation of nitrate reduction inside the plant to produce ammonia then amino acids. Similar induced in morphological characters of squash and other cucurbits plants of potassium foliar application has been reported by Abd El-Hamed and Elwan (2011), Kazem (2013), Shafeek et al (2013) and Pal et al(2016).…”
Section: Vegetative Growth Characteristicssupporting
confidence: 86%
See 2 more Smart Citations
“…They referred this enhancing effect to the physiological role of potassium in stimulating enzymes responsible for carbohydrate synthesis and production of energy as well as protein synthesis through its role in activation of nitrate reduction inside the plant to produce ammonia then amino acids. Similar induced in morphological characters of squash and other cucurbits plants of potassium foliar application has been reported by Abd El-Hamed and Elwan (2011), Kazem (2013), Shafeek et al (2013) and Pal et al(2016).…”
Section: Vegetative Growth Characteristicssupporting
confidence: 86%
“…This increment may be due to that plants need a high amount of potassium and other nutrients during flowering and fruit setting stages to perform the biological operations as increase in photosynthesis which couple with chlorophyll synthesis. (Pal et al,2016). An adequate quantity of potassium plays a principal role in plant growth and development by activating abundant enzymes which control cell osmoregulation and the stomatal movement during photosynthesis (Broadley et al,2009).…”
Section: Yield and Its Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects can vary greatly depending on hormone requirement, relative concentrations, and plant responses at different growth stages [29]. Many studies have focused the attention on the use of this phytohormone for improving the productivity and quality of several crop plants [30][31][32][33][34][35][36][37]. GAs have been commercially applied to control the vegetative growth of many horticultural crops.…”
mentioning
confidence: 99%
“…Furthermore, Kazemi (2013) on cucumber stated that potassium promotes photosynthesis and transport assimilates of the carbohydrates to the storage organs. Moreover, Pal et al (2016) found that applied plants with potassium increased protein synthesis and accelerating enzymes activity which responsible for biomass accumulation in cucumber fruits . Also , Abd-Alkarim et al (2017) on cucumber found that silicon increased fruit chemical composition, i.e., nitrogen , phosphorus , potassium and protein percentage.…”
Section: B Effect Of Foliar Spray With Yeast Extract and Potassium Smentioning
confidence: 99%